The political economy of international oil and the underdeveloped countries - Tanzer, Michael (Beacon Press, 1969)
Carlyle sdeath, further criticism of the book which most vividly expresses him in the heat and strength of his youth and earlier manhood, is not wanted. The Sartor Resartus has been more discussed than any other of his works, as he himself has been more talked of than any other writer of our time, and it will be of little use to add to the discussion here. There is, however, one addition which may be usefully made to the book, those passages, namely, from the Life and Reminiscences which bear on the creation of Teufelsdrockh, and on the trying adventures of the book, when finished, before it succeeded in finding a publisher and an audience.